2015
DOI: 10.1038/tp.2015.28
|View full text |Cite
|
Sign up to set email alerts
|

Increased functional connectivity in the resting-state basal ganglia network after acute heroin substitution

Abstract: Reinforcement signals in the striatum are known to be crucial for mediating the subjective rewarding effects of acute drug intake. It is proposed that these effects may be more involved in early phases of drug addiction, whereas negative reinforcement effects may occur more in later stages of the illness. This study used resting-state functional magnetic resonance imaging to explore whether acute heroin substitution also induced positive reinforcement effects in striatal brain regions of protracted heroin-main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 74 publications
2
31
0
1
Order By: Relevance
“…The putamen is part of a dopaminergic network involved in anticipation of reward and related emotions. Increases in the functional connectivity of this reward brain area have been associated with substance use disorders including cocaine (Konova et al, 2015) and heroine (Schmidt et al, 2015). Along with other areas involved in planning, attention and visual processing, higher activation of the putamen in smoking abstainers is related to increased salience of craving cues (McClernon et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The putamen is part of a dopaminergic network involved in anticipation of reward and related emotions. Increases in the functional connectivity of this reward brain area have been associated with substance use disorders including cocaine (Konova et al, 2015) and heroine (Schmidt et al, 2015). Along with other areas involved in planning, attention and visual processing, higher activation of the putamen in smoking abstainers is related to increased salience of craving cues (McClernon et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, techniques such as the assessment of resting state functional network connectivity (rsFNC) of the brain, derived from functional magnetic resonance imaging (fMRI), are emerging as possible alternatives with clinical applications (Fox et al, 2010; Lee et al, 2013b). Changes in rsFNC patients have been observed in many studies including traumatic brain injury (Mayer et al, 2011; Vakhtin et al, 2013), addiction (Chanraud et al, 2011; Claus et al, 2013; Schmidt et al, 2015), Alzheimer’s disease (Sheline and Raichle, 2013), bipolar disorder and schizophrenia (Chai et al, 2011; Das et al, 2014; Yu et al, 2011). In spite of the success achieved, there have been few systematic approaches comparing classification results as a function of differences in data processing.…”
Section: Introductionmentioning
confidence: 99%
“…Opiate-addicted individuals had weaker RSFC between the pACC with the dACC, DLPFC, medial PFC, and PCC/precuneus (Ma et al, 2010; Ma et al, 2015; Wang et al, 2013; Yuan et al, 2010); and between the caudate and DLPFC (middle frontal gyrus) (Wang et al, 2013). In ICA or other whole-brain approaches, compared with controls, opiate-addicted individuals had weaker resting-state functional connectivity of the ACC and basal ganglia regions (including the striatum) (Liu et al, 2011a; Ma et al, 2011; Schmidt et al, 2015). …”
Section: Evidence Of Resting-state Functional Connectivity Deficitmentioning
confidence: 99%
“…However, because this experiment was conducted in social drinkers (not in alcohol-addicted individuals), the potential relevance to addiction is unclear. Another study found that a heroin challenge (versus placebo) in opiate-addicted individuals strengthened connectivity within an ICA-defined basal ganglia network (including striatum) (Schmidt et al, 2015). Similarly, opiate-addicted individuals receiving high methadone doses showed higher ACC glutamate levels (Greenwald et al, 2015; Verdejo-Garcia et al, 2013).…”
Section: 0 Working Hypothesis: Abnormal Glutamatergic And/or Gabaementioning
confidence: 99%
“…A study in patients undergoing protracted heroinmaintenance also showed increased RFC of the putamen, which was associated with the reported effects of the drug (Schmidt et al 2015a). Another study by the same group investigated changes in connectivity with fMRI in response to fearful faces to test differences in stress reactivity.…”
Section: Neural Effects Of Pharmacological Interventionsmentioning
confidence: 98%